Saam Acupuncture for Treating Functional Dyspepsia: A Feasibility Randomized Controlled Trial. (29th June 2022) - Lee, Boram; Kwon, O.-Jin; Kim, Joo-Hee; Kang, Jung Won; Kim, Tae-Hun; Lee, Seunghoon; Kim, Jungeun; Kim, Ae-Ran; Jung, So Young; Park, Hyo-Ju; Choi, Sun-Mi
Abstract : Objective. Functional dyspepsia (FD) is a common gastrointestinal disorder that significantly affects sufferers' quality of life and increases the economic burden on society. Saam acupuncture, a form of traditional Korean acupuncture, is frequently used to treat FD in Korean medicine clinical settings. This study aimed to evaluate the feasibility and preliminary effectiveness and safety of Saam acupuncture for treating FD. Methods . We conducted a pilot, pragmatic, assessor-blinded randomized controlled trial. Patients with FD according to the ROME III criteria were randomly allocated to an acupuncture plus usual care group or a usual care group. Saam acupuncture based on individualized FD and systemic symptoms was conducted in the acupuncture group three times per week for 4 weeks. Study feasibility outcomes, including recruitment, completion, and acupuncture adherence rates, were calculated. In addition, preliminary evaluation of participant responses to the intervention was tested using the gastrointestinal symptom (GIS), FD-related quality of life (FD-QoL), visual analog scale (VAS), patient global assessment (PGA), and EuroQol-5 Dimensions (EQ-5D) scores. Results . Twenty-four participants who met the eligibility criteria were included. The recruitment and completion rates of the clinical trials were 60% and 79.2%, and the acupuncture adherence rate was 83.3%. Although there was no significant difference between the two groups in the dyspepsia symptoms as measured by GIS, VAS, and PGA at Week 4, significant differences were found between the two groups at the follow-up assessments (Weeks 8 and 12). In particular, the early satiety subscore of GIS was significantly improved in the Saam acupuncture group compared with the usual care group at Week 4. The quality of life measured by FD-QoL and EQ-5D improved only in the Saam acupuncture group, although there were no significant differences between the two groups. No adverse events related to Saam acupuncture were reported. Conclusions . Saam acupuncture can be a feasible, preliminarily effective, and safe treatment for FD. Further confirmatory trials with a larger sample size are needed to confirm its effectiveness and safety. The trail is registered with CRIS-KCT0000164, URL: https://cris.nih.go.kr/cris/search/detailSearch.do/2098 .